Involvement of WNT Signaling in the Regulation of Gestational Age-Dependent Umbilical Cord-Derived Mesenchymal Stem Cell Proliferation. (12th September 2017) - Iwatani, Sota; Shono, Akemi; Yoshida, Makiko; Yamana, Keiji; Thwin, Khin Kyae Mon; Kuroda, Jumpei; Kurokawa, Daisuke; Koda, Tsubasa; Nishida, Kosuke; Ikuta, Toshihiko; Fujioka, Kazumichi; Mizobuchi, Masami; et al.
Abstract : Mesenchymal stem cells (MSCs) are a heterogeneous cell population that is isolated initially from the bone marrow (BM) and subsequently almost all tissues including umbilical cord (UC). UC-derived MSCs (UC-MSCs) have attracted an increasing attention as a source for cell therapy against various degenerative diseases due to their vigorous proliferation and differentiation. Although the cell proliferation and differentiation of BM-derived MSCs is known to decline with age, the functional difference between preterm and term UC-MSCs is poorly characterized. In the present study, we isolated UC-MSCs from 23 infants delivered at 22–40 weeks of gestation and analyzed their gene expression and cell proliferation. Microarray analysis revealed that global gene expression in preterm UC-MSCs was distinct from term UC-MSCs. WNT signaling impacts on a variety of tissue stem cell proliferation and differentiation, and its pathway genes were enriched in differentially expressed genes between preterm and term UC-MSCs. Cell proliferation of preterm UC-MSCs was significantly enhanced compared to term UC-MSCs and counteracted by WNT signaling inhibitor XAV939. Furthermore, WNT2B expression in UC-MSCs showed a significant negative correlation with gestational age (GA). These results suggest that WNT signaling is involved in the regulation of GA-dependent UC-MSC proliferation.